1987
DOI: 10.1086/131990
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and nitrogen abundances in metal-poor dwarfs of the solar neighborhood

Abstract: We have analyzed spectra of 83 subdwarfs obtained with the Lick Observatory 3.1-m Shane telescope for C, N, and Fe abundances. Our stellar sample is composed principally of stars in the lowest metallicity domain, -1.5 > [M/H] > -3.2. Applying the model-atmosphere technique of spectrum synthesis to our intermediate-resolution spectra, we deduced [C/Fe] from the CH bands (X ~ 4300 À), [N/Fe] from the NH bands (X ~ 3360 À), and [Fe/H] from strong mostly Fe I features (3400 A < X < 3550 A). We find excellent agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 24 publications
10
87
1
Order By: Relevance
“…In the overlapping metallicity range, the thin disk stars reveal, on average, lower [C/Fe] ratios than the thick disk stars. In contrast, the study by Bensby & Feltzing (2006) From observations of the CH bands in 83 subdwarfs Carbon et al (1987) found [C/Fe] to be essentially constant and close to the solar value over the range −2.5 < [Fe/H] < −0.7. However, they noted an upturn in the [C/Fe] Spite et al (2005) from observations of the CH bands for the sample of 'unmixed' giant stars in the range −4 < [Fe/H] < −2.5.…”
Section: Introductionmentioning
confidence: 80%
“…In the overlapping metallicity range, the thin disk stars reveal, on average, lower [C/Fe] ratios than the thick disk stars. In contrast, the study by Bensby & Feltzing (2006) From observations of the CH bands in 83 subdwarfs Carbon et al (1987) found [C/Fe] to be essentially constant and close to the solar value over the range −2.5 < [Fe/H] < −0.7. However, they noted an upturn in the [C/Fe] Spite et al (2005) from observations of the CH bands for the sample of 'unmixed' giant stars in the range −4 < [Fe/H] < −2.5.…”
Section: Introductionmentioning
confidence: 80%
“…Our two most MP stars with thin-disk kinematics, HD105755 Mashonkina et al (2003). This star is also known for its extreme nitrogen overabundance, with [N/Fe] = 0.9 (Carbon et al 1987), and probably not representative of a standard evolutionary scenario for our Galaxy.…”
Section: Notes On Individual Starsmentioning
confidence: 93%
“…For more than 20 years, the nucleosynthetic origin of primary nitrogen, which is one of the most abundant and important elements in the Universe, for life in particular, has remained a deep mystery in astrophysics (Edmunds & Pagel 1978;Barbuy 1983;Carbon et al 1987;Thuan et al 1995;Izotov & Thuan 1999;Henry et al 2000). Nitrogen is mainly produced by the CN cycle of the CNO reactions which catalyze hydrogen burning in stars.…”
Section: The Context: Observations and Modelsmentioning
confidence: 99%